Leptin Modifies the Rat Heart Performance Associated with Mitochondrial Dysfunction Independently of Its Prohypertrophic Effects - Edna Berzabá-Evoli; Cecilia Zazueta; Jarumi Hishel Cruz Hernández; Nancy Patricia Gómez-Crisóstomo; Isela Esther Juárez-Rojop; Erick Natividad De la Cruz-Hernández; Eduardo Martínez-Abundis (International Journal of Endocrinology)
Background. Functional receptors for leptin were described on the surface of cardiomyocytes, and there was a prohypertrophic effect with high concentrations of the cytokine. Therefore, leptin could be a link between obesity and the prevalence of cardiovascular diseases. On the other hand, a deleterious effect of leptin on mitochondrial performance was described, which was also associated with the evolution of cardiac hypertrophy to heart failure. The goal of our study was to analyze the effect of the exposure of rat hearts to a high concentration of leptin on cardiac and mitochondrial function. Methods. Rat hearts were perfused continuously with or without 3.1 nM leptin for 1, 2, 3, or 4 hours. Homogenates and mitochondria were prepared by centrifugation and analyzed for cardiac actin, STAT3, and pSTAT3 by Western blotting, as well as for mitochondrial oxidative phosphorylation, membrane potential, swelling, calcium transport, and content of oxidized lipids. Results. In our results, leptin induced an increased rate-pressure product as a result of increased heart rate and contraction force, as well oxidative stress. In addition, mitochondrial dysfunction expressed as a loss of membrane potential, decreased ability for calcium transport and retention, faster swelling, and less respiratory control was observed. Conclusions. Our results support the role of leptin as a deleterious factor for cardiac function and indicates that mitochondrial dysfunction could be a trigger for cardiac hypertrophy and failure.